Shortage of antiseizure medication in Germany: How big is the problem? - Steidl, Josephine; Krebs, Sabine; Kostev, Karel; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2025)
Objectives: We determined the frequency of drug shortages of antiseizure medication (ASM) availability in Germany. Methods: Retrospective and descriptive analysis of databases of 2 pharmaceutical wholesalers in Germany with a market share of about 45% of the German market in July 2023 (chosen arbitrarily) focusing on antiseizure drug shortages (i.e. demand could not be met entirely) and disruptions (i.e. demand could not be met at all) on the level of formulations, ASM and of manufacturers. Results: 98/909 (10.8%) of formulations of ASM with Wholesaler A were listed with drug shortages and 131/872 (15%) of formulations were reported with drug shortages at Wholesaler B. 19 of 222 (8.6%) entire ASM at Wholesaler A and 12/213 (5.6%) of ASM with Wholesaler B were reported with drug shortages. 41/62 (66.1%) manufacturers at wholesaler A and 36/57 (63.2%) manufacturers at wholesaler B reported shortages. The three compounds affected most frequently by drug shortages were pregabalin, levetiracetam and carbamazepine. 1.7% (Wholesaler A) and 12.9% (Wholesaler B) of formulations were listed with disruptions. 16.7% (40/239) of ASM with drug shortages/disruptions were brand-name ASM and 83.3% (199/239) were generic ASM. Conclusions: 11% to 15% of ASM formulations had drug shortages in Germany in July 2023. Generic ASM were more frequently affected than brand-name ASM. About 2/3 of manufacturers were reported to have drug shortages.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Antiseizure medication; Drug shortages; Epilepsy

Surgical hematoma evacuation of cortical intracerebral hemorrhage ≥10 ml reduces risk of subsequent epilepsy by more than 70%: A retrospective monocenter study - Welte, Tamara; Steidl, Josephine; Stritzelberger, Jenny; Gollwitzer, Stephanie; Lang, Johannes; Reindl, Caroline; Rampp, Stefan; Maslarova, Anna; Brandner, Sebastian; Hock, Stefan; Mühlen, Iris; Dörfler, Arnd; et al. (European Journal of Neurology, 2022)
Aim: The aim of this study was to re-evaluate risk factors for post-ICH epilepsy (PICHE) and examine the impact of surgical hematoma evacuation on epilepsy development after ICH. Background and purpose: Epilepsy is a common complication after intracerebral hemorrhage (ICH). Information on risk factors is still scarce and the role of ICH evacuation remains uncertain. Methods: We retrospectively included patients with spontaneous ICH treated in our hospital in 2006–2019. Patients' medical records were analyzed. In addition, mailed questionnaires and telephone interviews were used to complete the dataset. Uni- and multivariable hazard ratios (HRs) were applied to investigate risk factors for PICHE and the impact of surgical ICH evacuation. Results: Among 587 ICH patients available for analyses, 139 (23.7%) developed PICHE (mean follow-up 1795 ± 1378 days). The median time of epilepsy onset was 7 months after ICH (range 1–132 months). Risk factors associated with PICHE were cortical hemorrhage (multivariable HR 1.65 [95% CI 1.14–2.37]; p = 0.008), ICH volume > 10 ml (multivariable HR 1.91 [95% CI 1.33–2.73]; p < 0.001) and acute symptomatic seizures (multivariable HR 1.81 [95% CI 1.20–2.75]; p = 0.005). Patients with cortical ICH > 10 ml who underwent surgical hematoma evacuation were less likely to develop epilepsy than those with conservative treatment alone (multivariable HR 0.26 [95% CI 0.08–0.84]; p = 0.025). Conclusions: Post-ICH epilepsy is frequent and predicted by large cortical ICH and acute symptomatic seizures. Hematoma evacuation reduced the risk of PICHE by more than 70% in patients with large cortical ICH. This finding could be considered in the clinical decision making on the acute treatment of ICH.
CRIS-Team Scopus Importer:2022-10-21
Keywords: CAVE score; hematoma evacuation; intracerebral hemorrhage; post-stroke epilepsy